Strategi Penyelesaian Eksekusi Hak Tanggungan Terhadap Benda Jaminan Dalam Pembiayaan Murabahah Pada Perbankan Syariah (Studi Kasus : PT Bank Syariah Indonesia Area Medan Kota) - M. Fauzan Rusyidi Nst; Mustafa Khamal Rokan (LPPM Universitas Labuhanbatu, 2022)
Â In Murabahah Financing, the execution of the guarantee can be carried out by fulfilling the conditions. The method used is a qualitative method by means of interviews, observations, and literature studies. Based on the results of the analysis, it is stated that if there is no ability and good intention of the customer in returning the financing, it has gone through restructuring. However, from these efforts, customers have not been able to fulfill their obligations. The guarantee execution procedure is through the Non-Litigation stage, namely the sale under the hands (Offsetting) in accordance with Article 20 paragraph (2) and (3) of the UUHT and through the Litigation stage (Legal/Court Line). The practice of auctioning the execution of Mortgage Guarantees is carried out in two ways, namely: First, the Bank submits a fiat application for Mortgage execution to the Religious Courts based on Article 14 paragraph (2) of the UUHT. Second, the Bank may also submit a request for an execution auction of the Mortgage object directly (parate execution) to the State Property and Auction Service Office (KPKNL) in accordance with Article 6 of the UUHT. Through the Mashalihul Mursalah theory by taking the philosophy of benefit for the people and the 'Urf theory in accordance with the qaidah